(untitled) (Investigación y Desarrollo, 2022)
The Differentiated Instruction (DI) approach addresses individual learner`s needs in a mixed ability class by focusing instruction on student learning profiles. The purpose of this study was to describe the effects of the implementation of four DI strategies suggested by Herrera (2011) in order to analyze their impact on students’ productive skills within two different educational settings: the high school and university. A total of 105 students and two English teachers participated in this study. An online survey assessed learners’ perceptions of the DI strategies. The results confirmed that the 4 DI strategies implemented in both settings had a positive effect on the development of students’ writing and speaking skills. This study concluded that there is not a universal, one-size-fits-all strategy for teaching that includes all students. In-depth knowledge of students’ needs, and interests is a starting point for addressing instruction in a more effective way. Finally, the DI approach is starting to emerge in Ecuadorian EFL classrooms, and teachers are showing interest in applying the corresponding strategies as an aid to student learning.